Mitigasi Risiko Pinjaman Online Ilegal dan Perlindungan Hukum bagi Ibu Rumah Tangga di Desa Sungai Gantang Kabupaten Indragiri Hilir - Darmiwati, Darmiwati; Rahmah, Siti; Wahyuni, Fitri; Wandi, Wandi; Syariffuddin, Syariffuddin; Jamri, Jamri (Penerbit Widina, Widina Media Utama, 2025)
The rise of illegal online lending practices in Indonesia has caused serious problems, particularly among housewives in rural areas who have low levels of digital literacy and legal understanding. This community service activity aims to mitigate the risks of illegal online lending by enhancing legal understanding and digital literacy among housewives in Indragiri Hilir District. The implementation methods include interactive socialisation, focused group discussions, and case study simulations relevant to the participants' daily lives. A total of 45 housewives actively participated in this activity, alongside community leaders and village officials as supporters. The results of the activity showed a significant increase in participants' knowledge, understanding, and legal awareness of the characteristics of illegal online loans, the legal mechanisms available if they become victims, and the importance of a critical attitude towards digital financial offers on social media. The outputs of the activity included the development of an educational module based on digital consumer law and the establishment of the Illegal Online Loan Awareness Forum as a space for ongoing education. In conclusion, the participatory approach to legal empowerment has proven effective in strengthening social protection for housewives from the trap of illegal online loans and serves as a model for community-based interventions that can be replicated in similar areas.ABSTRAKMeningkatnya praktik pinjaman online ilegal di Indonesia telah menimbulkan masalah yang serius, khususnya di kalangan ibu rumah tangga di wilayah pedesaan yang memiliki tingkat literasi digital dan pemahaman hukum yang rendah. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk melakukan mitigasi risiko pinjaman online ilegal melalui peningkatan pemahaman hukum dan literasi digital bagi ibu rumah tangga di Kabupaten Indragiri Hilir. Metode pelaksanaan meliputi sosialisasi interaktif, diskusi kelompok terfokus, dan simulasi studi kasus yang relevan dengan kehidupan sehari-hari peserta. Sebanyak 45 ibu rumah tangga terlibat aktif dalam kegiatan ini, bersama tokoh masyarakat dan perangkat desa sebagai pendukung. Hasil kegiatan menunjukkan peningkatan signifikan dalam pengetahuan dan pemahaman serta kesadaran hukum peserta terhadap ciri-ciri pinjaman online ilegal, mekanisme hukum yang dapat ditempuh jika menjadi korban, serta pentingnya sikap kritis terhadap tawaran keuangan digital di media sosial. Luaran kegiatan meliputi penyusunan modul edukatif berbasis hukum konsumen digital dan pembentukan Forum Waspada Pinjol Ilegal sebagai ruang edukasi berkelanjutan. Kesimpulannya, pendekatan partisipatif dalam pemberdayaan hukum terbukti efektif dalam memperkuat perlindungan sosial bagi ibu rumah tangga dari jerat pinjaman online ilegal dan menjadi model intervensi berbasis komunitas yang layak di replikasi di daerah serupa.